MENCEGAH FENOMENA FEAR OF MISSING OUT PADA REMAJA - Raka Rasyal; Muhammad Setiawan Sahib; Muhammad Alif Abdi Manaf; Ahmad Ridfah; Ismalandari Ismail (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
Fear of missing out is a great desire to stay connected with what other people are doing through cyberspace. This psychoeducation aims to add information to adolescents about the Fear of Missing Out phenomenon and how to prevent it. Psychoeducation was carried out by distributing posters and giving a survey using a Google form to several teenagers in Makassar and South Tangerang for three days. The results of implementing psychoeducation on 30 teenage respondents aged 17 to 20 years, namely psychoeducational activities provide information so that respondents become more aware of the Fear of Missing Out phenomenon and add insight. In addition, the insights obtained from psychoeducational activities are that respondents understand more about the Fear of Missing Out phenomenon and how to overcome it, the contents of the poster can be applied to themselves, know what to do when experiencing this situation, and get motivation after reading posters related to Fear of Missing Out prevention.